Design and development of a microcontroller-based automatic wet scrubber system for welding smoke control using CO and gas indicator sensors - Jufri Jufri; Enni Sulfiana; Saktiani Karim; Muhammad Ridwan Anwar; Rival Alviansyah; Bintang Jayakusuma; Yuda Agung Wirawan (Jurnal Polimesin, 2026)
Welding workshops are one of the work environments with a high potential for air pollution due to welding smoke containing heavy metal particles and hazardous gases such as Carbon Monoxide (CO). This research aims to design and build a wet scrubber-based welding smoke cleaning device that works automatically using a gas sensor and a microcontroller system. This system consists of an exhaust fan, a diaphragm pump, a drum filter containing activated charcoal and stone, and MQ-2 and MQ-7 sensors that detect smoke. The system automatically activates when hazardous gases are detected. System calculations show an air flow rate of 258.84 m³/hour and a pump water flow rate of 0.00208 m³/minute. This device was designed with space efficiency, low power consumption (90 W), and ease of maintenance in mind. Each experimental condition was tested for 10 minutes and repeated three times. MQ-2 and MQ-7 sensor readings were recorded at 1- second intervals. The inlet (Cin) and outlet (Cout) values were obtained from the average stabilized sensor readings measured before and after the activation of the wet scrubber system. The experimental results showed that the proposed system achieved relative reductions of up to 19.41% for smoke indicator readings and 17.55% for CO readings at full water flow rate, while reductions of 13.69% (smoke) and 15.28% (CO) were observed at half water flow rate. These results are based on sensor-based relative measurements and indicate the practical performance of the prototype system. This research is expected to provide a practical solution for maintaining air quality in small to mediumscale welding workshops.